POLITICAL CONNECTIONS, CORPORATE GOVERNANCE AND INVESTMENT EFFICIENCY: EVIDENCE FROM MALAYSIAN FIRMS (Malaysian Management Journal, 2024)
This study investigates the moderating role of corporate governance in the relationship between political connections and investment efficiency. Using a sample of Malaysian publicly listed firms from 2001- 2017, we find that political connections are negatively correlated with firm investment efficiency. Moreover, the relationship is robust with the inclusion of corporate governance mechanisms, which moderated the potential consequences of agency problems in politically connected firms. The evidence suggests that corporate governance appears to be an effective mechanism to improve investment efficiency in politically connected firms. Consistent with the agency costs of free cash flow theory, we also discover that political connections have a more significant detrimental impact on overinvestment compared to their positive influence on underinvestment. Nevertheless, the interaction results in corporate governance hold regardless of overinvestment or underinvestment. Further analysis reveals that domestic institutional ownership, Big Four auditors, and audit committees are effective governance mechanisms, whereas similar observations do not hold for foreign institutional ownership, board size, board independence, and director ownership. Resultantly, high direct policy relevance is provided for governance practitioners and policymakers in monitoring the investment activities of PCFs.